Coronin-1C and RCC2 guide mesenchymal migration by trafficking Rac1 and controlling GEF exposure - Williamson, Rosalind C.; Cowell, Christopher A. M.; Hammond, Christina L.; Bergen, Dylan; Roper, James; Feng, Yi; Rendall, Thomas C. S.; Race, Paul R.; Bass, Mark D. (Journal of cell science, 2014)
Sustained forward migration through a fibrillar extracellular matrix requires localization of protrusive signals. Contact with fibronectin at a protruding tip activates Rac1, and for linear migration it is necessary to dampen Rac1 activity in off-axial positions and redistribute Rac1 from non-protrusive membrane to the leading edge. We identify interactions between Coro1C, RCC2 and Rac1 that focus active Rac1 to a single protrusion. Coro1C mediates release of inactive Rac1 from non-protrusive membrane and is necessary for Rac1 redistribution to a protrusive tip and fibronectin-dependent Rac1 activation. The second component, RCC2, attenuates Rac1 activation outside the protrusive tip by binding to the Rac1 switch regions and competitively inhibiting GEF action, thus preventing off-axial protrusion. RNAi of Coro1C or RCC2 causes loss of cell polarity that results in shunting migration in 1D or 3D culture systems. Furthermore, morpholinos against Coro1C or RCC2, or mutation of any of the binding sites in the Rac1/RCC2/Coro1C complex delays the arrival of neural crest derivatives at the correct location in developing zebrafish, demonstrating the critical role in migration guidance in vivo.